Strategi Bimbingan Klasikal Teknik Sinema Edukasi Topeng Malangan untuk Memperkuat Sikap Asertif Siswa SMP - Ista Yuliarti; Arbin Janu Setiyowati; Fitri Wahyuni (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Assertive behavior is defined as an individual's ability to honestly express their feelings or emotions through their preferred form of expression. Assertive behavior is an important aspect that needs attention, especially for individuals undergoing education, such as middle school students. One characteristic of middle school students is their tendency to have unstable emotions, making them easily influenced by peers. The purpose of this study is to conduct a literature review on classical guidance services and educational cinema techniques to strengthen students' assertive attitudes. This study is a type of SLR (Systematic Literature Review) research. The literature review found 11 articles: 5 articles discussed classical guidance services for assertive behavior, 2 articles addressed educational cinema techniques for assertive behavior, and 4 articles explored the values of Malangan mask dance that could be applied to students' assertive behavior. The conclusion of this study is that the values embedded in the Malangan Mask Dance can help individuals develop honesty, courage, empathy, politeness, responsibility, and self-confidence. These values align with the principles of assertive behavior, enabling the creation of classical guidance services using Malangan Mask educational cinema techniques to strengthen assertive attitudes. The findings of this study can serve as a theoretical foundation for future research, as further data-based studies are still needed to determine whether the implementation of classical guidance services using Malangan Mask educational cinema techniques significantly impacts students' assertive behavior.